2003
DOI: 10.1021/je0201323
|View full text |Cite
|
Sign up to set email alerts
|

Surface Tension of Pure Liquids and Binary Liquid Mixtures

Abstract: The pendant drop method, combined with efficient temperature control of the measuring cell, allows high precision in surface tension measurements. The surface tensions of heptane, toluene, N,N-dimethylformamide, cyclohexane, N-methyl-2-pyrrolidone, and propanone were measured as a function of temperature using the pendant drop method. The results were compared with literature data. The surface tension and density of toluene + heptane and N,N-dimethylformamide + toluene at atmospheric pressure were measured ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
64
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(68 citation statements)
references
References 56 publications
1
64
1
Order By: Relevance
“…For instance, different methods used by the individual groups, the impurities in the sample and the susceptibility to water affect the measurements. The suitability of the experimental method used and the appropriate handling has been verified by comparing measured data of three different (standard) solvents (water, toluene and diisodecyl phthalate) at different temperatures with reported data in literature, [108][109][110] see À -based ILs are hygroscopic and hydrophilic as has already been shown in one of our previous works. 2 Despite the fact that some investigators 111 have indicated that water has a negligible effect on the surface tension, it is important, in all cases, but especially with hydrophilic ILs to report the water content, since most of the thermophysical properties are affected by the presence of water.…”
Section: Surface Tensionmentioning
confidence: 68%
“…For instance, different methods used by the individual groups, the impurities in the sample and the susceptibility to water affect the measurements. The suitability of the experimental method used and the appropriate handling has been verified by comparing measured data of three different (standard) solvents (water, toluene and diisodecyl phthalate) at different temperatures with reported data in literature, [108][109][110] see À -based ILs are hygroscopic and hydrophilic as has already been shown in one of our previous works. 2 Despite the fact that some investigators 111 have indicated that water has a negligible effect on the surface tension, it is important, in all cases, but especially with hydrophilic ILs to report the water content, since most of the thermophysical properties are affected by the presence of water.…”
Section: Surface Tensionmentioning
confidence: 68%
“…It should be noted that, although the trend of variation of surface entropies and surface enthalpies for all mixture are nearly the In all systems the experimental surface tension data show negative deviation from additivity, indicating an enrichment of one component in the liquid-vapor interface. A quantitative description of this phenomenon can be achieved by the Gibbs adsorption isotherm for an ideal mixture [24,25],…”
Section: Resultsmentioning
confidence: 99%
“…The method is based on analysis of pendant drop profile [58,59]. The profile is scanned by a camera and geometry of a drop is analyzed by computer program.…”
Section: Pendant Drop Methodsmentioning
confidence: 99%
“…It is a compound with well-known properties, therefore a large amount of data on the surface tension has been found in literature. Although the methods of measurement are different (capillary rise method [65,66], pendant drop method [59], Wilhelmy plate/Du Nouy ring [60]), the obtained surface tension values at the same temperatures are practically the same. It can be seen that the proposed GCM method (Fig.…”
Section: Calculated and Literature Values Of Surface Tensionmentioning
confidence: 96%